Paragraphs as episodes : distinguishing paragraphs in Biblical Hebrew narrative text on the basis of linguistic devices - Yoo, Chang Keol (Stellenbosch : Stellenbosch University, 2008)
Thesis (MA (Ancient Studies))--Stellenbosch University, 2008.